Authoritarian Leadership in Collaborators by John Hodge 2011 - Nia Arista Syafitri; Muhd. Al-Hafizh (Universitas Negeri Padang, 2019)
The purpose of this analysis is to expose the issue of authoritarian leadership and to know the contribution of the character, setting and stage direction in revealing the meaning of authoritarian leadership. This analysis is related to the concept of Power and Country by Niccolo Machiavelli that is supported by the text and context based interpretation. The result of this analysis shows that the strategies in maintaining the power legitimacy done by a state leader can be seen through performing autocracy and personality cult.